A REVIEW OF STOCK MARKET IMPACT OF ENVIRONMENTAL CATACLYSMS AND LESSONS FOR INVESTORS - Ngwakwe, Collins C (Copernican Journal of Finance & Accounting, 2023)
The objective of this paper is to present a review analysis of stock market impact of environmental disaster with the factors that orchestrate the impact, and to offer a novel framework for investors and managers. The paper applied an in-depth empirical review and synthesis method. Findings from the review and synthesis of empirical literature provide strong evidence that environmental disasters have diverse effects on the stock markets with majority of the literature reporting adverse effects on the stock markets. Additionally, findings are more preponderant on short run impact than on long run effects. Findings also show that environmental disasters may offer unique arbitrage opportunities for short-selling investors. The paper concludes by highlighting the capacity of environmental finance as one of the catalysts to bolster corporate adaptive capacity to environmental disaster. Furthermore, the degree of environmental disaster impact on stock market may depend on factors such as the type of environmental disaster, geographical location of environmental disaster, economic sector, stage of economic development, length of disaster and intensity of disaster. Accordingly, the paper develops a framework, which is recommended as a model for further research agenda on environmental disaster effect on stock markets.